CELLULAR IMMUNITY ACTIVATION METHOD BY STIMULATING RD1 COMPLEX PROTEINS AS VIRULENCE MARKER ON Mycobacterium tuberculum TO ESTABLISH DIAGNOSIS ON TUBERCULOSIS AND LATENT TUBERCULOSIS INFECTION - Setiabudi, Rebekah; Mertaniasih, Ni Made; Didik Handijatmo, Didik; Setyoningrum, Retno Asih (Indonesian Journal of Tropical and Infectious Disease, 2015)
This study was intended to invent a simpler and more affordable method to establish diagnosis on Tuberculosis (TB) and Latent Tuberculosis infection (LTBI). Similar to âQuantiferon TB Gold In Tubeâ (QFT-GIT) and T.SPOT.TB methods, the researchers also utilized âearly secreted antigenic target 6kDaâ (ESAT-6) and âcultur filtrate protein 10kDaâ (CFP-10) proteins to be induced on the specimen. ESAT-6 and CFP-10 are commercial products used to induce interferon gamma (INF-Î³) which were to be read using sophisticated and expensive equipment. This study was intended to conduct an analysis on effective cocktail protein modification, i.e. ESAT-6, CFP-10 and Ag85A/B/C, with high validity to detect cellular immunity activity through in vitro examination on peripheral blood monocyte cells of Tuberculosis-suspected patients or patients with latent tuberculosis infection. Peripheral Blood Monocyte Cells (PBMCs) activity on children tuberculosis patient or Latent Tuberculosis Infection (LTBI), adult tuberculosis patient or LTBI, which induced by cocktail protein modification and not induced, were analyzed microscopically. The activity of PBMCs on children and adult tuberculosis patient or LTBI induced by RD1 secretory proteins: ESAT-6, CFP-10, Ag85A/B/C was higher compared to PBMCs which had not been induced by the secretory proteins. Cellular debris and monocyte cells with abnormal shapes were found on PBMCs which had been induced by RD1 secretory proteins at 8 th day after culture.